RICE SAMPLE VAPORIATION METHOD ON METER TESTING RESISTIVE WATER CONTENT BASED ON ULTRASONIC MIST - Syahwir, Irawati Dewi; Dinny, Fauzia Nur; Ihsan, Firman Khoirul (Program Studi Fisika Universitas Negeri Jakarta, 2023)
Percentage moisture content is an important factor in assessing the quality and quantity of agricultural commodities, such as rice. The measurement of moisture content is very important to evaluate the moisture content of rice, which directly affects its quality. However, the measurement of moisture content takes a long time, so it is necessary to have an evaporation method to shorten the time so that the moisture content of the sample is as required. In this study, the method chosen was the evaporation method with ultrasonic mist. The results showed that this ultrasonic fog controller evaporation system successfully increased the moisture content of rice samples according to the criteria needed to be used in resistive-type moisture meter testing. The ultrasonic mist controller evaporation system can increase the water content of rice samples according to the criteria needed for use in resistive-type moisture meter testing, with an average increase of 0.9% within 15 minutes, 3.4% within 30 minutes, and 4.1% within 1 hour.